Enhanced Carrier Transport Properties in GaN-Based Metal-Insulator-Semiconductor High Electron Mobility Transistor with SiN/Al2O3 Bi-Layer Passivation. (1st January 2018) - Chang, S.-J.; Jung, H.-W.; Do, J.-W.; Cho, K. J.; Kim, J.-J.; Jang, Y. J.; Yoon, H. S.; Ahn, H.-K.; Min, B.-G.; Kim, H.; Yang, J.-M.; Kwon, H.-S.; et al.
Abstract : The impacts of SiN/Al2 O3 bi-layer passivation on the carrier transport characteristics in GaN-based metal-insulator-semiconductor high electron mobility transistors (MISHEMTs) were studied. Various mechanical stresses, as measured by micro-Ramam spectroscopy, were introduced on the GaN channel according to the different passivation systems. The SiN dielectric layer deposited by plasma enhanced chemical vapor deposition on top of the GaN capping layer resulted in compressive stress. On the other hand, the Al2 O3 passivation layer deposited by atomic layer deposition on SiN layer generated tensile stress, which compensated the compressive stress produced by the SiN layer. The correlation between the applied mechanical stress induced by the deposited dielectric layers and device performance of the GaN-based HEMT was also investigated. When a slight tensile stress was applied on the GaN channel through the bi-layer passivation, the carrier transfer characteristics were improved in terms of carrier concentration at the AlGaN/GaN interface, as well as carrier mobility and sheet resistance compared to the high compressive stress condition. These results show that the mechanical stress engineering via optimized passivation process is a promising technique for the improvement of the device performance in GaN-based MISHEMTs.